(untitled) (Vietnam Journal of Agriculture and Environment, 2023)
Vibrio bacteria are among the most serious pathogens of aquatic creatures. Furthermore, they can cause diseases at any stage in the lifecycle of aquaculture animals with mortality up to 100%, which results in great economic losses. To control these agents, the currently widely-applied solution is to use antibiotics, which cause environmental pollution and drug resistance in microorganisms. Another solution is biological products, which have not yet been proven highly effective. In this context, there have been studies showing that a promising new solution is to use a sediment bioelectrochemical system (SBES) though only at small scales (<1 L). In this study, we evaluated the Vibrio-bacteria-controlling capability of a sediment bioelectrochemical system (SBES) integrated into a 10 L scale model that mimics a water column in a real-life brackish aquaculture pond. The viability of three strains Vibrio harveyi NBRC15634 (Vh), Vibrio parahaemolyticus NBRC12711 (Vp), and Vibrio parahaemolyticus CED (wild-type, isolated from actual ponds) when exposed to the filtrates obtained from the cathode solution and the anode solution of the system, was determined over time by plate counting on the specific TCBS medium. The results showed that the density of Vibrio bacteria did not change when exposed to the filtrate from the cathode but decreased significantly, up to 99% when treated with the filtrate from the anode of SBES, while no similar phenomenon occurred with the control. Even when the two Vibrio strains were present simultaneously, the SBES reduced the densities of Vp (in CFU/mL) by approximately 2 logs, and completely eliminated Vh after 3 hours. In summary, using the SBES will be a potential method to efficiently control pathogenic Vibrio bacteria in brackish aquaculture while offering simple implementation.